Confronting Christian Penal Charity: Neoliberalism and the Rebirth of Religious Penitentiaries - Hallett, Michael A. (Social justice, 2018)
This article addresses the rise of Christian seminary programs in US prisons as a function of penal regime change in late-modern corrections. The article documents the neoliberal roots of faith-based programming in US prisons, featuring increased reliance upon religious volunteerism as a structural charity in correctional budgeting. Federal revocation of Pell Grant eligibility for convicted felons in 1994 has produced a de facto monopoly of Christian educators promulgating an exclusively sectarian framing of offender rehabilitation. Although faith-based programming can offer effective counternarratives to punitive justice that dramatically improve the well-being of prisoners who freely volunteer, overreliance upon Christian instruction in US prisons fosters a coercively sectarian framing of rehabilitation and a newly privatized mechanism for inmate education.